Além das medidas: abordagens lúdicas e desafios da OBMEP na compreensão do conceito de área - Silva, Silmara Louise da (Universidade Federal de São Carlos, 2023)
This project consisted of conceiving, implementing, and applying a didactic sequence that used diverse pedagogical approaches, including the use of manipulative materials, to explore concepts and problems related to the field of polygons. The activities were carefully planned to progressively increase the level of challenge, aiming to stimulate students to develop strategic thinking skills in solving specific problems from the Brazilian Public School Mathematics Olympiad (OBMEP). The didactic sequence was applied to 8ᵗʰ grade students at a municipal school in the city of Poços de Caldas during the second semester of 2022 and the first semester of 2023, and the results were analyzed and validated from the perspective of didactic engineering.
Beyond measures: playful approaches and challenges of OBMEP in understanding the concept of area
Keywords: Áreas de polígonos; Sequência didática; OBMEP; Polygon areas; Teaching strategies; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM